Thalassemia: Pathophysiology, Diagnosis, and Advances in Treatment - Idris Zubairu Sadiq; Fatima Sadiq Abubakar; Hauwa Salisu Usman; Aliyu Dantani Abdullahi; Bashiru Ibrahim; Babangida Sanusi Kastayal; Maryam Ibrahim; Hassan Aliyu Hassan (Thalassemia Reports)
Thalassemia represents a diverse group of inherited hematological disorders characterized by defective globin chain synthesis, leading to chronic anemia and associated complications. The complicated pathophysiology of beta-thalassemia involves genetic mutations or rarely deletions of the beta-globin gene on chromosome 11 whereas alpha-thalassemia involves deletions in the HBA1 and HBA2 genes or occasionally alterations to the DNA sequence in or around these genes. These mutation and deletion effects disrupt the balance of α/β-globin chain production, resulting in ineffective erythropoiesis, hemolysis, and a cascade of clinical manifestations including anemia, bone deformities, and iron overload. Advances in diagnostic techniques have enhanced our ability to detect and characterize these mutations, facilitating early and accurate diagnoses. Current management strategies encompass regular blood transfusions, the use of hydroxyurea to improve hemoglobin levels, and iron chelation therapy to prevent iron-related organ damage. Moreover, other therapeutics such as thalidomide for those not responding to hydroxyurea, Sirolimus for patients with immunodeficiencies, and use of vitamin E as an antioxidant have proven to be effective. Innovative therapies such as gene therapy and bone marrow transplantation offer promising curative potential, opening a new era in the treatment of thalassemia. This review focuses on pathophysiological mechanisms underlying thalassemia, explores the diagnostic methodologies, and highlights recent advancements in therapeutic approaches.